Biological Strategies to Minimize Fertilizer Use in Maize: Efficacy of Trichoderma harzianum and Bacillus subtilis - de Lima Gonilha, Dalilla Berlanda [UNESP]; Santos, Carlos Henrique Barbosa [UNESP]; Frezarin, Edvan Teciano [UNESP]; Siqueira, Josiane Soares [UNESP]; Rigobelo, Everlon Cid [UNESP] (MDPI, 2024)
The present study investigated the efficacy of Trichoderma harzianum and Bacillus subtilis in minimizing phosphorus fertilizer use in maize cultivation. Maize plants, cultivar Bm207, were subjected to 10 treatments with varying levels of phosphorus fertilization (0, 50, and 100%) and inoculation with B. subtilis, T. harzianum, or both. The plant growth parameters, including the height, stem diameter, shoot, and root dry weight, root volume, phosphorus content in the soil and plant tissues, and chlorophyll and carotenoid content, were evaluated. Treatments without mineral fertilization showed the lowest values for most parameters, despite the microbial inoculation. The combination of 100% mineral fertilizers with microbes did not improve the plant growth compared with the controls. However, the treatments with 50% mineral fertilization along with microbial inoculation generally maintained parameter values similar to those of the 100% fertilized control, suggesting the potential for reducing fertilizer doses by 50% without compromising plant development. Inoculation with B. subtilis and T. harzianum coupled with the use of mineral fertilizers improved the soil phosphorus availability compared to fertilizer application alone. This study highlights the potential of these microorganisms to enhance soil fertility and plant growth while reducing chemical fertilizer use in maize cultivation, although further field research is necessary to verify the long-term sustainability of this approach.
Keywords: environmental impact; mineral fertilizers dose; reduction costs